Clinicopathological significance of cancer stem cells marked by CD133 and KAI1/CD82 expression in laryngeal squamous cell carcinoma - Yu, Lan (BioMed Central, 2014)
BACKGROUND: Presently, CD133 is one of the hottest markers to characterize cancer stem cells and KAI1/CD82 is reported as an important marker for the metastasis and prognosis of many cancers. The purpose of our study is to explore the relationship between cancer stem cells (CSCs) marked by CD133 and KAI1/CD82 expression and the clinicopathological characteristics of patients with laryngeal squamous cell carcinoma (LSCC). METHODS: Immunohistochemical analysis was used to detect the expression of CD133 and KAI1/CD82 in 83 archival surgical specimens of human LSCC and 83 cases of normal laryngeal tissues. RESULTS: In LSCC, positive rates of 49.4% and 41.0% were obtained for CD133 and KAI1/CD82, respectively. The expression of CD133 in LSCC tissues was significantly higher than that in normal tissues (P < 0.001), and the expression of CD133 was positively associated with pTNM stage (P = 0.005), pathological grade (P = 0.001), and lymph node metastasis (P < 0.001). The reduced expression of KAI1/CD82 was present in LSCC tissues. The positive rate of KAI1/CD82 expression was negatively correlated with pTNM stage (P = 0.014), pathological grade (P < 0.001), and lymph node metastasis (P = 0.007). A correlation analysis showed that there was a negative relationship between the expression of CD133 and KAI1/CD82 protein in LSCC tissues (P < 0.001). By Kaplan-Meier analysis, the expression of CD133 was negatively correlated with overall survival (OS) (log-rank = 40.949, P < 0.001) and disease-free survival (DFS) (log-rank = 39.307, P < 0.001) time of LSCC. The expression of KAI1/CD82 was positively correlated with OS (log-rank = 40.279, P < 0.001) and DFS (log-rank = 39.271, P < 0.001) time of LSCC. Cox regression analysis: the expression of CD133 and KAI1/CD82, and pTNM stages were independent prognostic factors of LSCC (P < 0.05). CONCLUSIONS: Thus the detection of CD133 and KAI1/CD82 proteins may be used as a potential indicator of LSCC prognosis.